Enhancing engine power and torque and reducing exhaust emissions of blended fuels derived from gasoline-propanol-nano particles. (15th February 2022) - Karimi Abiyazani, Narges; Pirouzfar, Vahid; Su, Chia-Hung
Abstract: The present research aims to study the impact of different gasoline additives and engine conditions on engine performance and combustion emissions. To this end, the experimental design and study with related modeling and optimization techniques are applied for appropriate and accurate evaluations and analysis. The D-optimal methodology is used to optimize engine power and exhaust emission through implementing the general blended fuel preparation and engine conditions considering the five main parameters, including choice of n-propanol loading percentage, type of nanoparticle materials, particle parentage in the blend, engine speed, and throttle. Findings by modeling analysis showed that the quadric and cubic terms of these five variables had significant and essential effects. The optimal conditions are obtained in blend of 8 wt% of n-propanol and 0.2 wt% of aluminum oxide (Al2 O3 ), and engine speed and throttle of 1750 rpm and 26%, respectively. Under these conditions, the model estimated the CO, CO2, HC, and NOx emissions of 2.24, 5.09, 68.94, and 152.7 ppm, respectively. Employed experimental study, optimization procedure, and developed models can be used as a valuable technique for preparing modified gasoline fuels with effective performance. Highlights: Novel and effective nano particles additives are introduced to add gasoline-n propanol blend. D-optimal design and experimental study is performed to prepare propanol + MgO/Al2 O3 and compare with gasoline. Modeling and optimization of the response including emissions and engine performance are implemented. Verification and accuracy analysis are performed for models. additives result in higher engine performance and fuel combustion emissions efficiency than gasoline.